2006
DOI: 10.1029/2004jd005550
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur, sea salt, and radionuclide aerosols in GISS ModelE

Abstract: [1] We simulate a suite of aerosols in the new GISS ModelE GCM: present-day sulfur species and the natural species sea salt, radionuclides 7 Be (stratospheric source), and 210 Pb (derived from 222 Rn from soils). The natural species are used to test the model and to help diagnose the anthropogenic sulfur species. Model improvements over previous versions include increased vertical resolution, addition of a stratiform dissolved species budget (DSB), better tracer coupling to the boundary layer, and an improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
250
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 208 publications
(258 citation statements)
references
References 73 publications
8
250
0
Order By: Relevance
“…This simplified emission scheme has successfully been used by numerous modelling studies (e.g. Feichter et al, 1991;Liu et al, 2001;Koch et al, 2006). 210 Pb has a similar geochemical behaviour to 10 Be or 7 Be.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This simplified emission scheme has successfully been used by numerous modelling studies (e.g. Feichter et al, 1991;Liu et al, 2001;Koch et al, 2006). 210 Pb has a similar geochemical behaviour to 10 Be or 7 Be.…”
Section: Methodsmentioning
confidence: 99%
“…Pedro et al, 2011) require the use of a global model or at least one including one hemisphere. Comparison with observations has shown that they are much more sensitive to uncertainties in scavenging and atmospheric transport than short-lived tracers emitted from Earth's surface (Brost et al, 1996;Koch et al, 2006;Liu et al, 2001). Optimally a model version including the middle atmosphere would be used, describing full stratospheric dynamics and allowing for a better representation of the Brewer-Dobson circulation and hence tracer transport.…”
Section: Introductionmentioning
confidence: 99%
“…7 Be and 210 Pb have been simulated in global models, and used as passive tracers for the validation of deposition parameterizations (e.g., Brost et al, 1991;Liu et al, 2001;Feichter et al, 1991;Koch et al, 1996Koch et al, , 2006. Recently, simulation of 7 Be and 210 Pb have been introduced into the ECHAM5-HAM (Heikkilä et al, 2008(Heikkilä et al, , 2009).…”
Section: Simulation Of 210 Pb and 7 Bementioning
confidence: 99%
“…The production rates for 7 Be were taken from Masarik and Beer (1999). The 210 Pb/radon source is from soils and was taken to be 1 atoms cm −2 s −1 , following Feichter et al (1991);Liu et al (2001); Koch et al (2006). 7 Be and 210 Pb are not explicitly distributed into the aerosol modes of the ECHAM5-HAM.…”
Section: Simulation Of 210 Pb and 7 Bementioning
confidence: 99%
“…Feichter et al, 1996;Koch et al, 2006; with different degrees of complexity concerning oxidant availability, aqueous phase chemistry, dry and wet deposition. Major efforts have been made in recent years to improve atmospheric aerosol modeling on the global and regional scale.…”
Section: Introductionmentioning
confidence: 99%